Integration of Joyful Learning and Deep Learning in Modern Education - Marzius, Marzius; Syaiful M; Valensy Rachmeditha (ICSIGER- International Conference on Science and Emerging Technology, 2025)
This study aims to describe the strategy of implementing Joyful Learning integrated with the principles of Deep Learning at SD Negeri 1 Tegineneng and to analyse its impact on student engagement and understanding. Using a qualitative descriptive method, data were collected through classroom observations, in-depth interviews with teachers, and analysis of documents such as lesson plans, learning media, and student work. Observation sheets were used to record student activities and teaching strategies, while interview guidelines explored teachers' perceptions of the effectiveness and challenges of implementation. The results showed that teachers applied various Joyful Learning methods, including educational games, group discussions, storytelling, simple experiments, and mini-projects, which were effective in increasing student motivation and participation. Observation data showed high levels of engagement, with 85% of students active during educational games and more than 70% involved in discussions and collaborative activities. The integration of Deep Learning through reflective questions, analytical tasks, and inquiry-based activities encouraged a deeper understanding of concepts. These findings support humanistic, constructivist, and sociocultural theories, demonstrating that enjoyable and meaningful learning can improve cognitive achievement and holistic learning experiences.